Third Person Pronouns in Grassfields Bantu - Hyman, Larry (My University, 2018)
In this paper I have two goals. First, I propose a reconstruction of the pronoun system of Grassfields Bantu, direct reflexes of which are found in Eastern Grassfields, with a close look at the pronoun systems, as reflected across this varied group. Second, I document and seek the origin of innovative third person pronouns in Western Grassfields. While EGB languages have basic pronouns in all persons, both the Momo and Ring subgroups of WGB have innovated new third person (non-subject) pronouns from demonstratives or perhaps the noun 'body'. However, these languages show evidence of the original third person pronouns which have been restricted to a logophoric function. I end with a comparison of the Grassfields pronouns with nearby Bantoid and Northwest Bantu languages as well as Proto-Bantu.
Keywords: Grassfields Bantu; Pronouns; Third person